Improved methods for controlling interconnected DC microgrids in rural villages - Pascal Hategekimana; Adrià Junyent-Ferré; Etienne Ntagwirumugara (AIMS Energy, 2024)
Interconnected Microgrid (IMG) networks have been suggested as the best to build electrical networks in remote villages far from the main electricity grid by interconnecting the nearby distributed energy resources (DERs) through power electronic converters. Interconnecting different DERs results in voltage deviation with unequal power-sharing, while voltage performance is a significant challenge. The control strategies for these converters are essential in the operational stability of any IMG network under study. In this paper, we propose an improved droop control method aiming to manage the power flow among the IMGs by maintaining the constant desired voltages in the network with minimum voltage deviation, resulting in the minimization of power losses. We found that the minimum voltage deviation at the load side (converter-3) was between 0.58 and 0.56 V, while the voltage deviation for both converter-1 and converter-2 remained below 0.5 V. This leads to efficient voltage regulation, resulting in the stability of an IMG network. To verify the feasibility of this method, MATLAB/SIMULINK has been used.